Sexual Dimorphism of a Genetic Risk Score for Obesity and Related Traits among Chinese Patients with Type 2 Diabetes - Xiaomu Kong (Obesity Facts, 2019)
Background: Obesity is more prevalent in men than in women in China, especially within the middle-aged population. Objectives: The present study aims to determine the contribution of sexual dimorphisms to obesity and related traits in terms of the mechanisms involving the obesity-related genetic variants among patients of Chinese Han ancestry with type 2 diabetes. Method: In the Chinese National Diabetes and Metabolic Disorders Study, 2,555 out of 4,036 patients with type 2 diabetes were treatment naive, including 1,142 men and 1,413 women. Single-nucleotide polymorphisms (SNP) from 18 genomic loci previously found to be associated with obesity-related traits were successfully genotyped, and a genetic risk score (GRS) was constructed by summing the risk alleles for obesity. Results: Single SNP analysis showed that genetic variants in SLC30A10, TMEM18, GNPDA2, PRL, TFAP2B, BDNF, MTCH2, FTO, and MC4R were nominally associated with waist circumference (WC), BMI, and risk for abdominal or general obesity in the untreated patients with type 2 diabetes, as well as in the total group of patients with type 2 diabetes (untreated and treated) (p < 0.05). Interactions between sex and SNP in PRL, MTCH2,and FTO were detected (p < 0.05). In the untreated patients with diabetes, the GRS was nominally associated with WC (β = 0.0032, SE = 0.0011; p = 0.003), BMI (β = 0.0030, SE = 0.0013; p = 0.027), and increased risk for abdominal (OR = 1.08; 95% CI 1.02–1.13; p = 0.004) or general obesity (OR = 1.07; 95% CI 1.02–1.13; p = 0.011) in men but not in women. GRS-sex interactions were detected in the determinant of WC (p = 0.019) and abdominal obesity (p = 0.016). Among patients aged 30–60 years, GRS was found to be significantly associated with WC (β = 0.0050, SE = 0.0016; p = 0.002) and abdominal obesity (OR = 1.10; 95% CI 1.04–1.17; p = 0.001) and nominally associated with BMI (β = 0.0057, SE = 0.0020; p = 0.005) and general obesity (OR = 1.07; 95% CI 1.01–1.14; p = 0.027) in men, whereas in women none of the associations were detected. GRS-sex interactions were present in the determinant of WC (p = 0.015), BMI (p = 0.032), and abdominal obesity (p = 0.012). Among patients aged 60 years or older, neither an association of GRS with obesity-related traits nor GRS-sex interactions were detected. Conclusions: Genetic factors contribute to obesity-related traits in a sex-dependent pattern among middle-aged Chinese, and men tend to be more susceptible to the genetic risk of obesity.